(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Article explores how the expansion and diversification of the service sector contribute to improving the socio-economic well-being of individuals, especially in developing economies. The paper examines the growing dominance of services in global GDP and employment and highlights the critical role of sub-sectors such as finance, education, healthcare, tourism, and ICT in enhancing income, providing decent work, and reducing multidimensional poverty. By analyzing case studies, economic indicators, and academic literature, the study identifies enabling conditions—such as digital infrastructure, inclusive policies, and skill development— that are necessary to unlock the full poverty-reduction potential of the service industry. The work also acknowledges the limitations and inequalities in access to service-based benefits and provides policy recommendations for creating inclusive, sustainable growth through services.